The Effect of Experimental Escherichia coli Infection on Some Blood Parameters and Histological Changes in Male Rats: Hayder AL – Zamely * Shayma’a Z falh - AL – Zamely, Hayder (The Iraqi Journal of Veterinary Medicine, 2011)
This study was carried out to investigate the effect of experimental infection by Escherichia coli on some blood parameters and histopathological changes in male rats to reach this objective twenty male rats (Rattus norvigicus) were divided into two groups, housed under same conditions of water, feed, temperature, light and humidity. The first one served as control group, while the second was experimentally infected with Ecoli by administration of 2ml / rat of (1×109) colony forming unit/ml of E-coli. Five days later blood were obtained from animals by cardiac puncture to measure the total and differential white blood cells count hemoglobin concentration packed cells volume red blood cells count, and thrombocytes count. One animal from each group was killed and histopathological examination was done for intestine kidney liver and spleen to detect the effect of infection on these organs. The results revealed a significant increase in total leukocytes count (P<005) in infected group while the differential count showed a significant increase in neutrophils and significant decrease in lymphocytes (P< 0.05) in same group. There were a significant decrease in hemoglobin concentration packed cell volume and non significant decrease in red blood cells count. While thrombocytes count showed a significant decrease in infected group compared with control group (P<0.05). The histopathological examination of infected male rats intestine was demonstrated mild diffuse inflammation which include increased numbers of neutrophile in tissue intraepithelial lymphocytes and goblet cells In kidney renal tubules showed extensive epithelial swelling with decreased lumen space and generalized necrotic changes with interstitial hemorrhage in renal cortex. In liver hepatocytes were swollen with decreased sinusoidal spaces and widely distributed necrotic foci were seen. There is extensive splenic necrosis with infiltration of leukocytes from white pulp to red pulp of spleen.